The knowledge and perceptions of healthcare workers regarding obstetrical anal sphincter injuries. A practice audit from a resource-constrained settingAJOG Global Reports at a Glance - Randall Kegan Hammond, MbChB, FCOG, MMed; Thinagrin Dhasarathun Naidoo, MbChB, LRCPI&SI, FCOG, FMAS, PhD (Elsevier, 2021)
BACKGROUND: We hypothesized that knowledge regarding obstetric anal sphincter injuries amongst healthcare workers in our setting is limited. A lack of knowledge would result in worsened clinical outcomes and proving this knowledge deficiency would allow us to institute educational programs to improve outcomes. OBJECTIVE: This study aimed to assess the knowledge and perceptions of healthcare workers regarding obstetrical anal sphincter injuries in a resource-limited setting. STUDY DESIGN: Questionnaires assessing the knowledge in classification, diagnosis, and management of obstetrical anal sphincter injuries were completed by 290 doctors and nurses involved in conducting vaginal deliveries at various levels of care (primary, district, regional, tertiary) in a resource-limited setting. Moreover, confidence in managing obstetrical anal sphincter injuries was assessed. RESULTS: Although the healthcare workers' knowledge of anatomy was poor, most healthcare workers knew how to define obstetrical anal sphincter injuries and classify these injuries. Most healthcare workers considered obstetrical anal sphincter injuries serious complications and perceived that patients with obstetrical anal sphincter injuries were best managed at a regional- or tertiary-level hospital. There was variation in choice of suture material and methods of repair, with most healthcare workers lacking confidence in managing obstetrical anal sphincter injuries and 96.9% of healthcare workers indicating a need for further training. Most healthcare workers felt that perineal support was the best intrapartum preventative strategy against obstetrical anal sphincter injuries. CONCLUSION: Here, it was likely that knowledge and confidence in managing obstetrical anal sphincter injuries in most resource-limited settings were suboptimal, highlighting a need for ongoing training.